2016
DOI: 10.1161/strokeaha.115.010753
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Glucose on Outcomes in Patients Treated With Mechanical Thrombectomy

Abstract: 6-8 perhaps because, among patients treated with intravenous thrombolysis, reperfusion occurs in only 40% to 50% and documentation of reperfusion timing and extent imprecise.Accordingly, the advent of mechanical thrombectomy (MT), which more frequently achieves reperfusion and permits more exact characterization of reperfusion timing and extent, offers an opportunity to more clearly evaluate the potential Background and Purpose-Sparse data are available regarding the association between hyperglycemia and outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(37 citation statements)
references
References 35 publications
3
32
1
1
Order By: Relevance
“…In accordance with previous studies, our study also found that old age [27], severe neurological deficits [27], high baseline glucose level [28], pneumonia [29,] and sICH [30] were independent predictors for poor functional outcome. Moreover, small baseline infarct core (ASPECTS 8-10) [31], successful revascularization (mTICI 2b-3) [27,32], good collateral status (2-3) [33,34], and OTT ≤6 h [27,35,36] were protective factors.…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with previous studies, our study also found that old age [27], severe neurological deficits [27], high baseline glucose level [28], pneumonia [29,] and sICH [30] were independent predictors for poor functional outcome. Moreover, small baseline infarct core (ASPECTS 8-10) [31], successful revascularization (mTICI 2b-3) [27,32], good collateral status (2-3) [33,34], and OTT ≤6 h [27,35,36] were protective factors.…”
Section: Discussionsupporting
confidence: 91%
“…In this study there were no significant associations between admission glucose levels and patient outcome. This is in contrast to previous reports where admission hyperglycemia was associated with worse outcome in both alteplase and endovascular thrombectomy patients 1–3. Mechanisms of acute hyperglycemia-related damage include early platelet and leucocyte adhesion and accumulation in cortical microvessels, along with leucocyte extravasation, blood–brain barrier disruption, and postcapillary microthrombosis 19 24.…”
Section: Discussioncontrasting
confidence: 76%
“…Admission hyperglycemia is associated with worse outcome in patients with ischemic stroke treated with intravenous alteplase and endovascular thrombectomy 1–3. In these patients, admission hyperglycemia may indicate either ‘stress’ hyperglycemia or pre-existing impaired glucose metabolism 4.…”
Section: Introductionmentioning
confidence: 99%
“…These cases should not be considered in isolation, as a poor outcome does not necessarily indicate that such physicians are providing a lower quality of care, but rather that they have a different patient mix than the trials that were used to create the benchmarks. 7,8,10,11,[13][14][15]18,20,[143][144][145] Adjusting for risk and severity may be helpful in assessing local outcomes compared with other institutions and benchmarks. Endovascular QI case review triggers and key process metrics are summarized in Table 3.…”
Section: Triggers For Reviewmentioning
confidence: 99%